Variation of the foF2 parameter during fluctuating activity: Prediction with IRI-2012 compared to measured data from Ouagadougou inosonde station during solar cycles 21 and 22 - Diabaté, Abidina; Zerbo, Jean Louis; Ouattara, Frédéric (Vietnam Journal of Earth Sciences, 2019)
In this paper, we review on diurnal variations of the foF2 ionospheric parameter predicted by the IRI-2012 model, and data from Ouagadougou ionosonde station located in the crest of the Equatorial Anomaly (Lat: 12.5°N; Long: 358.5°E, dip: 1.43°) during fluctuating geomagnetic activity conditions for the solar cycles 21 and 22. Our investigations are focused on the electrodynamic aspects, the influence of the ionospheric electric currents as well as the variations of the hourly values given by model and experimental measurements. A comparative study pointed out that the IRI-2012 model, through its URSI and CCIR subroutines, gives a good prediction of the critical frequency of the F2 layer between 0700 TL and 0000 TL. In addition, IRI -2012 tries to reproduce, as best as possible, the vertical drift E × B during minimum, decreasing phase, winter, and autumn. However, there is no effect of drift during the other seasons and solar cycle phases. A last, the model does not take into account the PRE phenomenon observed in autumn and the influence of the equatorial electrojet in this ionospheric zone.ReferencesAcharya R., Roy B., Sivaraman M.R., 2010. Dasgupta A. An empirical relation of daytime equatorial total electron content with equatorial electrojet in the Indian zone. J Atmos Terr Phys, 72(10), 774–780.Acharya R., Roy B., Sivaraman M.R.; Dasgupta A., 2011. On conformity of the EEJ based Ionospheric model to the Fountain effect and resulting improvements. J Atmos Terr Phys, 73, 779-784.Adeniyi J.O., Oladipo O.A., Radicella S.M., 2005. Variability of fof2 and comparison with iri model for an equatorial station. The Abdus Salam International Centre for Theoretical Physics, IC/2005/085, http://www.ictp.it/~pub_off.Adeniyi1 J.O., Oladjipo O.A., Radicella S.M., 2005. Variability of foF2 and comparison with IRI model for an equatorial station. The Abdus Salam International Centre for Theoretical Physics, IC/2005/085.Bilitza D., et al., 2014. The International Reference Ionosphere 2012-a model of international collaborationI.  J. Space Weather Space Clim, 4, A07.Bilitza D., Reinisch B.W., 2008. International Reference Ionosphere 2007: Improvements and new parameters. Adv. Space Res, 42, 599–609.Farley D.T., Bonell E., Fejer B.G., Larsen M.F., 1986. The Prereversal Enhancement of the Zonal Electric Field in the Equatorial Ionosphere. J Geophys Res, 91(A12), 13,723–13,728.Faynot J.M., Villa P., 1979. F region at the magnetic equator. Ann Geophys, 35, 1–9.Fejer B.G., 1981. The equatorial ionospheric electric fields: A review. J Atmos Terr Phys, 43, 377.Fejer B.G., Farley D.T., Woodman R.F., Calderon C., 1979. Dependence of equatorial F region vertical drifts on season and solar cycle. J Geophys Res, 84, 5792.Legrand J.P., Simon P.A., 1989. Solar cycle and geomagnetic activity: A review for geophysicists. Part I. The contributions to geomagnetic activity of shock waves and of the solar wind. Ann. Geophys, 7, 565–578.Obrou K.O., 2008. Contribution à l’amélioration du modèle "International Reference Ionosphere" (IRI) pour l’ionosphère équatoriale. Thèse de doctorat Université de Cocody,  Abidjan, Côte d’Ivoire.Ouattara F., 2009. Contribution à l’étude des relations entre les deux composantes du champ magnétique solaire et l’Ionosphère Equatoriale. Thèse de Doctorat d’Etat ès Sciences, Université Cheikh Anta Diop, Dakar, Sénégal.Ouattara F., 2013. IRI-2007 foF2 Predictions at Ouagadougou Station during Quiet Time Periods from 1985 to 1995. Archives of Physics Research, 4, 12–18.Ouattara F., Amory-Mazaudier C., 2009. Solar–geomagnetic activity and Aa indices toward a Standard.  J. Atmos. Terr. Phys, 71, 1736–1748.Ouattra F., Nanéma, 2014. Quiet Time foF2 Variation at Ouagadougou Station and Comparison with TIEGCM and IRI-2012 Predictions for 1985 and 1990. Physical Science International Journal, 4(6), 892–902.Oyekola  O.S., Fagundes P.R., 2012. Equatorial F2-layer variations: Comparison between F2 peak parameters at Ouagadougou with the IRI-2007 model.  Earth, Planets Space, 64, 553–566.Rishbeth H., 1971. The F-layer dynamo. Planet, Space Sci, 19, 263.Vassal J.A., 1982. The variation of the magnetic field and its relationship with the equatorial electrojet in Senegal Oriental. Annals of Geophysics, Tome French, 38.Zerbo J.L., Amory-Mazaudier C. Ouattara F., Richardson J., 2012. Solar Wind and Geomagnetism, toward a Standard Classification 1868-2009.  Ann Geophys, 30, 421–426. http://dx.doi.org/10.5194/angeo-30-421-2012.Zerbo J.L., Amory-Mazaudier C., Ouattara F., 2013. Geomagnetism during solar cycle 23: Characteristics. J. Adv. Res, 4(3), 265–274. Doi:10.1016/j.jare.2013.08.010.Zerbo J.L., Ouattara F., Zoundi C., Gyébré A., 2011. Solar cycle 23 and geomagnetic activity since 1868. Revue CAMES serie A, 12(2), 255–262.